Building a resilient supply chain: Mitigating risks in label-holder production - Ulfah, Maria; Bahauddin, Achmad; Ekawati, Ratna; Sonda, Atia; Muharni, Yusraini; Fachrur, Aditya Rahadian (Universitas Sultan Ageng Tirtayasa, 2024)
This study investigates risk mitigation strategies within the label holder supply chain at a company specializing in convection-produced label holders. The House of Risk approach will be used to identify and prioritize potential risks and their sources throughout the supply chain activities, as defined by the Supply Chain Operation Reference (SCOR) method. Common supply chain risks include torn mica, detached stitches, and improper strap lengths. The risk identification process within the label holder supply chain activities resulted in 30 risk events, 27 risk agents, and 13 prioritized risk mitigation actions. These actions include regular routine machine maintenance, employee briefings, identifying backup suppliers, consistent performance monitoring, station coordination before production, machinery and tool upgrades for quality assurance, yearly shutdowns/maintenance, establishing customer contracts, user feedback coordination, training for raw material receiving personnel, implementing periodic product testing, enacting efficient inventory management practices, and improving finished goods quality management.